2009
DOI: 10.1590/s1413-70542009000100025
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação química de geléias de manga formuladas com diferentes níveis de cascas em substituição à polpa

Abstract: RESUMOObjetivou-se, neste estudo, avaliar a qualidade de geléias formuladas com níveis de 0 %, 25 %, 50 %, 75 % e 100 % de cascas em substituição à polpa de manga (Mangifera indica L. cv. Haden). Os critérios de qualidade utilizados foram os teores de umidade, cinzas, proteínas, lipídios, carboidratos totais, açúcares totais, açúcares redutores, sacarose, vitamina C, fibra insolúvel, pectina, acidez titulável e sólidos solúveis nas polpas e cascas das mangas e nos diferentes tratamentos. Observou-se que nos tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
18

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 4 publications
2
12
0
18
Order By: Relevance
“…After peel analysis, it was observed that the moisture content was 11% lower than the one found for the pulp. Similar results were observed by Gondim et al (2005) when analyzing moisture content of avocado pulp and peel (84 and 77%, respectively) and pineapple (86 and 78%, respectively) and by Damiani et al (2009) who reported a moisture content of mango pulp and peel 81,98 and 77,41%, respectively. However, Gondim et al (2005) showed that not all fruits present this type of behavior.…”
Section: Chemical Characteristics Of Peel and Pulp From Cajá-mangasupporting
confidence: 84%
See 4 more Smart Citations
“…After peel analysis, it was observed that the moisture content was 11% lower than the one found for the pulp. Similar results were observed by Gondim et al (2005) when analyzing moisture content of avocado pulp and peel (84 and 77%, respectively) and pineapple (86 and 78%, respectively) and by Damiani et al (2009) who reported a moisture content of mango pulp and peel 81,98 and 77,41%, respectively. However, Gondim et al (2005) showed that not all fruits present this type of behavior.…”
Section: Chemical Characteristics Of Peel and Pulp From Cajá-mangasupporting
confidence: 84%
“…Damiani et al (2009) observed an increase in the protein content after incorporating mango peel to the jelly formulation. However, the authors reported a noticeable decrease of these contents when compared to the in natura fruit.…”
Section: And As a Result To A Concentration Of The Other Constituenmentioning
confidence: 90%
See 3 more Smart Citations